The hive - Lyga, Barry; Baden, Morgan (KCP Loft, an imprint of Kids Can Press, 2019)
"It's the near future -- the day after tomorrow -- and the government has shut down online bullying once and for all. With BLINQ, its new social media platform, users can "like" or "share," but they can also "condemn" posts -- and if condemns reach a certain level, users can exact punishment from the original poster in real life. No more anonymous trolling! Instead... hive justice. Seventeen-year-old Cassie McKinney is angry at everything. She's just lost her beloved father, a cult hero in the hacking world. She's been uprooted to a new apartment and -- worse -- a new school. Cassie is barely enduring senior year when she's drawn into a powerful group of girls and their effort to make their posts go viral. Cassie's just trying to be funny when she posts a cutting BLINQ. But when that BLINQ goes viral in all the worst ways, she becomes the target of a furious mob. Abandoned by her friends, betrayed by the system, and bristling at the injustice of it all, Cassie goes on the run. In the shadows, she finds people to help her hide. If she wants to clear her name, though, she will have to work with them to unravel a conspiracy beyond her imagination."--